"Natural" Climate Solutions Could Speed Up Mitigation, With Risks. Additional Options Are Needed. Issue 4 (21st April 2020) - Crusius, John
Abstract: Mitigation of climate change by intentionally storing carbon in tropical forests, soils, and wetlands and by reducing greenhouse gas fluxes from these settings has been promoted as rapidly deployable and cost‐effective. This approach, sometimes referred to as "natural climate solutions, " could keep post‐industrialization warming below 1.5 °C, when coupled with reductions in fossil fuel emissions, as confirmed here with a simple numerical model of future emissions. However, such mitigation could cease in response to changes in future climate, land use, or natural resource policies, or there could be CO2 released from reservoirs of stored carbon. Model simulations suggest cumulative emissions could be similar, under scenarios where carbon storage ceases, or stored carbon is released, to emissions expected in the absence of any natural mitigation. If climate change is to be minimized, no‐regrets approaches to natural mitigation should be considered (e.g., by reducing deforestation), as emissions targets that could limit warming to 1.5 °C cannot be met without mitigation of this magnitude. However, additional mitigation options should also be evaluated that can reduce CO2 emissions and remove CO2 from the air (and store it permanently). Plain Language Summary: One option for fighting climate change involves "natural climate solutions" that would remove atmospheric CO2 by storing carbon in tropical forests, soils, and wetlands and would minimize greenhouse gas fluxes from such environments. With a simple computer code to predict future emissions, I confirm that such natural mitigation could, along with reductions in fossil fuel emissions, help keep the average global post‐industrialization temperature rise below 1.5 °C and could help delay impacts of climate change. However, future changes in climate, land use, or natural resource policies could cause natural mitigation to cease and emissions to increase, and modeling suggests levels could approach those expected in the absence of natural mitigation, which would negate much of the intended benefit. We should prioritize "no‐regrets" natural mitigation, including stopping deforestation, that can provide time to develop other needed mitigation options to remove atmospheric CO2 and permanently store it. Key Points: Natural mitigation of climate change, when coupled with fossil fuel emission reductions, could help to minimize warming Natural mitigation could cease, which could cause CO2 emissions to revert to levels similar to those without natural mitigation Other solutions that can reduce CO2 emissions rapidly and remove CO2 from the atmosphere and permanently store it are needed